Aktualisasi Public Relation dalam mewujudkan perbankan syariah yang inovatif dan responsif - Fadhilah, Moh Nur (Maliki Interdisciplinary Journal, 2025)
Islamic banking in this era must certainly be a financial institution that is able to adapt to the current situation and conditions, because currently Islamic banking is experiencing very rapid development, In the increasingly advanced digital era, technological innovation is a challenge and also an opportunity for Islamic banking to exist in society both nationally and internationally, good communication is certainly also the key for Islamic banking to be responsive and innovative, of course in this digital era by providing education about financial literacy to the community is a form of effective and innovative communication to realize responsive Islamic banking.